A natural sustained-intestinal release formulation of red chili pepper extracted capsaicinoids (Capsifen®) safely modulates energy balance and endurance performance: a randomized, double-blind, placebo-controlled study - Roopashree, N.; Syam, Das S.; Krishnakumar, I. M.; Mala, K. N.; Fleenor, Bradley S.; Thomas, Jestin (Frontiers in Nutrition, 2024)
Overweight and obesity are major public health concerns, with a sharp increase in prevalence over the last few decades. The primary cause is an imbalance between calorie intake and expenditure due to a rise in calorie-rich processed food and reduced physical activity. Energy balance in humans involve complex processes including thermogenesis, a crucial factor in regulating energy expenditure. In this randomized, double-blinded, placebo-controlled, 3-arm, 3-sequence study, we investigated the efficacy of Capsifen ® (CapF), a pungency-masked sustained-intestinal release formulation of red chili extract, on energy expenditure, fat oxidation, and endurance using the Quark C-PET system in healthy overweight participants, with and without exercise. In the study, 105 healthy participants were randomized to receive either placebo 100 mg/day, CapF 100 mg/day, or CapF 200 mg/day for 28 days. CapF demonstrated a dose-dependent response to increase energy expenditure and fatty acid oxidation with a concomitant reduction in body weight. Both CapF 100 and CapF 200 also increased the time to exhaustion. These results demonstrate the plausible efficacy of CapF in energy expenditure and physical performance in otherwise healthy adults who have high body mass index.